LITTER ACCUMULATION AND DECOMPOSITION IN FOUR DIFFERENT FOREST FORMATION - Cunha Neto, Felipe Vieira (2013)
http://dx.doi.org/10.5902/1980509810549The aim of this study was to quantify the litter layer on the soil and its decomposition rate, in four different forest types: wild stands of Acacia mangium, Mimosa artemisiana Heringer & Paula and Eucalyptus grandis x Eucalyptus urophylla, and a secondary forest at Fazenda Cachoeirão in the municipality of Além Paraíba, Minas Gerais state. In each forest formation, there were two